Genotypic characterization and novel multilocus sequence types of exoU+ Pseudomonas aeruginosa from different clinical infections and environments - Othman, Hemin E.; Miller, Eric L.; Jubrael, Jaladet MS.; Roberts, Ian S. (Innovaciencia, 2018)
Introducción: The exoU gene, a marker for highly virulent strains of Pseudomonas aeruginosa, is the major contributor to a wide varietyof healthcare-associated infections. Methods: In this study, the antibiotic susceptibility profile, prevalence and genotyping of exoU+ P.aeruginosa were demonstrated. A total of 101 isolates of P. aeruginosa were analysed from different clinical and environmental sources. Results: The antibiotic susceptibility profile classified these isolates as extensively drug resistant (35.6%), multidrug resistant (40.5%) and non-multidrug resistant (23.7%). The prevalence of exoU gene was screened by PCR and 23 exoU+ genotypes were detected which all were clinical isolates. Multilocus sequence typing (MLST) analysis of seven loci assigned these exoU+ genotypes to 21 sequence types (STs) from which 16 new STs were identified. The prevalent STs were ST-308 and ST-235. Phylogenetic analysis using the concatenated nucleotide sequences of the seven housekeeping genes, exoU and the ITS region differentiated these exoU+ strains into five main groups. However, distinct evolutionary origins for some new sequence types were also indicated. Conclusions: The studied isolates showed the coexistence of exoU- and exoU+ genotypes of clinical P. aeruginosa in Kurdistan with a majority of MDR and XDR pattern. The prevalent STs found in other hospitals worldwide and at the international level.
Keywords: Pseudomonas aeruginosa; PCR; exoU; MLST; Phylogenetic diversity